Smart accounting practices for small online businesses in Malaysia - Che Hassan, Anita (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Running a small online business in Malaysia can be exciting, with flexible hours, endless growth potential, and the joy of doing what you love. But let’s be honest, keeping track of your finances can be confusing, especially if you are not from accounting background. The good news is, with the right accounting practices in place, you can stay on top of your profit and make smarter business decisions. Unfortunately, many small online business owners overlook the importance of basic accounting. This is often because they think it is too complex, or because they are too busy managing orders, customers, and marketing.